“The golden mean” in views of mufti Galimjan Barudi: attitude to religious-legal schools in traditions of Russian Muslims - Nail B Abulhanov; Rinat A Nabiev (RUDN Journal of Russian History, 2018)
The article is devoted to the study of the topic of the day - the formation of the tradition of Russian Muslims on the issues of the attitude to the religious-legal schools on the example of the views of Galimjan Barudi, the outstanding religious figure of the 19th - early 20th centuries. The article touches upon his views on the important issues for Muslims of the Russian Empire, his reformist views on the attitude of Muslims towards the traditional religious-legal schools, in particular his view of the Hanafi religious-legal school, which is the most widespread among Russian Muslims. There are examined his achievements in the field of improving the Muslim education. The article demonstrates the scientist’s contribution to the formation of a new system of education of the Muslim peoples of the Russian Empire of the late 19th - early 20th centuries, based on the principles of reformation, “Jadidism”. Galimjan Barudi, the creator of the famous madrassah “Muhammadiya”, took an active part in these processes; he was the author of many scientific works devoted to reforming not only the educational system of Muslims of Russia, but the entire way of life of the Muslim peoples, especially the peoples of the Volga-Ural region of the country. The article reflects Galimjan Baroudi’s point of view on one of the most burning theological and legal issues - the possibility of ijtihad in the contemporary Muslim society, the “closing of the ijtihad gates”, since this issue was crucial in the theological disputes between the reformist direction of “Jadidism” and the traditionalist direction of “kadimism”. In addition to purely scientific research, these issues affected broad strata of the Muslim population, which was reflected in the publishing and educational activities of Galimjan Barudi. There is considered the issue of the possibility of changing the provisions of religious-legal schools in the spirit of the new time, in accordance with the circumstances of the changing socio-political and economic relations. The article provides Galimjana Barudi’s fatwas on various issues and analyzes their compliance with the traditional Hanafi law. There is reflected Galimjan Barudi’s general attitude to the Hanafi madhhab, as well as his attitude to reformation among Muslims of Russia in the 19th and early 20th centuries.